Antimicrobial potential and screening of phytochemical compounds of Lantana camara Linn. - Musyimi, David M.; Opande, George T.; Chesire, Jane (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Plants have a great number of chemicals that can be exploited as valuable sources of natural antibiotics and pesticides. Lantana camara has numerous potent phytochemicals that could be exploited in plant disease control and protection thereby reducing the indiscriminate use of synthetic pesticides. The effectiveness of extracts varies with its concentration and the kind of bacteria used in the study. Little research has documented the antimicrobial properties of Lantana camara plant varieties in Kenya against soil phytopathogens such as Pseudomonas syringae and Phytopthora infestans. This study was carried out to investigate on the antimicrobial potential of Lantana camara on the growth of Pseudomonas syringae and Phytopthora infestans and qualitative analysis of its phytochemical compounds. Roots and leaves were collected, shade dried and ground into fine powder and extracted by cold extraction method with 70% ethanol. Thereafter 10 %, 5% and 2.5% concentration of leaf extracts were constituted and distilled water used for control experiment. The experiment was arranged in a completely randomized design with three replicates. Disc diffusion method was used to assess antimicrobial activity of this plant by measuring the inhibitory growth zones formed around paper discs. Data obtained was subjected to Analysis of Variance and the means were separated and compared using the least significant difference at p< 0.05. The leaves extract treatments significantly reduced the growth of Pseudomonas syringae and Phytopthora infestans with increase in extract concentration, even though there were no significant differences between the two test microbes. Phytochemical analysis revealed the presence of alkaloids, flavonoids, saponins, tannins, phenols, cardiac glycosides, terpenoids and absence of steroids in the leaves and roots of the plant. Therefore it can be ascertained that certain active ingredients are present in the roots and leaves ‘crude extract of Lantana camara and have the potential to be exploited for manufacture of pesticides for control of diseases associated with Pseudomonas syringae and Phytopthora infestans.